Analisis Kinerja Teknologi Informasi Pada Universitas Jember Menggunakan Metode It Balanced Scorecard - Fajrin Nurman Arifin; Miftahul Jannah Asy'ari; Oktalia Juwita (Journal of Applied Computer Science and Technology, 2020)
In the face of the development of ICT (Information and Communication Technology) in tertiary institutions which is increasing, so that it requires an IT performance analysis method that can assess company performance accurately and thoroughly. This research was conducted to determine the extent of IT performance, whether it has met the needs and business strategies of tertiary institutions and IT strategies, and which still need improvements and improvements. In addition, the results of the analysis can be used as a basis as a reference for improving IT performance in Jember University. The purpose of using the IT Balanced Scorecard method is to analyze the IT performance of Jember University from four perspectives, namely: the perspective of the company's contribution, the perspective of user orientation, the perspective of operational improvement, and the perspective of future orientation. From the results of measurements that have been carried out it is known that the overall IT performance of Jember University is quite good, this is indicated by the results of the IT Balanced Scorecard size generated from each perspective.